Penggunaan Gadget di Kalangan Anak SD dan Tantangan dalam Lingkungan Sekolah - Maulian Fadli; Latifatu Qolbi; Kardilla Mutiasya; Salimatul Hayati; Elsa Tionita; Husnatul Azizah (Pusat Riset dan Inovasi Nasional, 2025)
The rapid advancement of digital technology has significantly influenced children's lives, including within elementary school environments. Gadgets offer access to interactive learning resources but also pose risks of addiction, reduced social skills, and impaired concentration if not properly managed. This study adopts a literature review method to analyze gadget usage patterns, the challenges faced by schools, and effective management strategies. The findings indicate that although educational applications can enhance students' learning interest, gadgets are more frequently used for entertainment purposes. A lack of supervision and coordination between schools and parents exacerbates these negative impacts. This research recommends clear school policies, wise integration of technology into the curriculum, and increased parental involvement. The results are expected to provide comprehensive insights and practical suggestions for educational stakeholders to foster a supportive learning environment in the digital age.